2002
DOI: 10.1046/j.1475-1313.2002.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic effects of GABA‐transaminase inhibitors in the treatment of epilepsy: ocular perfusion and visual performance

Abstract: Vigabatrin is a GABA (gamma-aminobutyric acid) transaminase inhibitor that elicits an antiepileptic effect by enhancing inhibitory neurotransmission in the brain. Vigabatrin has been previously associated with concentric peripheral visual field loss and visual electrophysiological abnormalities. Recently, visual function deficits of the central retina have been identified in a proportion of patients receiving vigabatrin; these include disturbances in colour perception, contrast sensitivity and short-wavelength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…The Nrf2 knockout mice did improve significantly over five trials to the level of the saline-treated wild type mice indicating that they can learn and swim as well as the wild type mice and therefore it appears that they do not have impairments in their motorabilities. There are reports of vision defects in individuals taking valproic acid, however it is related to long term treatment and to the GABAergic effects of valproic acid (Hosking and Hilton, 2002; Tilz et al, 2007). Since the water maze test was run 6 days after the valproic acid exposure, there is no longer GABA agonist action.…”
Section: Discussionmentioning
confidence: 99%
“…The Nrf2 knockout mice did improve significantly over five trials to the level of the saline-treated wild type mice indicating that they can learn and swim as well as the wild type mice and therefore it appears that they do not have impairments in their motorabilities. There are reports of vision defects in individuals taking valproic acid, however it is related to long term treatment and to the GABAergic effects of valproic acid (Hosking and Hilton, 2002; Tilz et al, 2007). Since the water maze test was run 6 days after the valproic acid exposure, there is no longer GABA agonist action.…”
Section: Discussionmentioning
confidence: 99%
“…9,21,22 In fact, measurements of visual acuity suggested that the deficit might not be limited to the periphery. 11,22 Visual deficits were associated with decreases in amplitude of the photopic ERG, flicker ERG, and oscillatory potentials. 13,22 The light/dark ratio of standard EOG measurements also was decreased even in some patients with no detected visual field loss, suggesting it may provide an early indicator of visual dysfunction.…”
Section: Retinal Cell Damagementioning
confidence: 99%
“…29 Retinal hypoxia also could occur in VGB treatment as indicated by the decrease in ocular perfusion 11 and the EOG alteration 10 representative of the relationship between the retinal pigment epithelium and photoreceptors. In this context, note that an epileptic patient (Case 3) treated with VGB and carbamazepine for 75 months had a retinal detachment before the age of 28 years, although it is unclear whether it was related to the VGB treatment.…”
Section: Fig 6 Ultrastructural Alterations Of Photoreceptors and Retmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered GABA uptake or metabolism is the method used to manage a wide range of conditions, including epilepsy . One of these drugs, vigabatrin, a selective GABA‐degradation enzyme inhibitor causes permanent peripheral visual field deficits, retinal electrophysiological changes and other visual disturbances . Although the exact mechanism is unknown, the inhibited enzyme, GABA transaminase, is essential for recycling the GABA carbon skeleton (succinate) which would be an energy source for the retina .…”
Section: The Visual Process and Neurotransmissionmentioning
confidence: 99%